Sex-specific echocardiographic reference values: the women's point of view. Issue 10 (October 2018) - Petitto, Marta; Esposito, Roberta; Sorrentino, Regina; Lembo, Maria; Luciano, Federica; De Roberto, Anna Maria; La Mura, Lucia; Pezzullo, Enrica; Maffei, Silvia; Galderisi, Maurizio; Lancellotti, Patrizio
Abstract : N/A: Clinical presentation, diagnosis and outcomes of cardiac diseases are influenced by the activity of sex steroid hormones. These hormonal differences explain the later development of heart diseases in women in comparison with men and the different clinical picture, management and prognosis. Echocardiography is a noninvasive and easily available technique for the analysis of cardiac structure and function. The aim of the present review is to underline the most important echocardiographic differences between sexes. Several echocardiographic studies have found differences in healthy populations between women and men. Sex-specific difference of some of these parameters, such as left ventricular (LV) linear dimensions and left atrial volume, can be explained on the grounds of smaller body size of women, but other parameters (LV volumes, stroke volume and ejection fraction, right ventricular size and systolic function) are specifically lower in women, even after adjusting for body size and age. Sex-specific differences of standard Doppler and Tissue Doppler diastolic indices remain controversial, but it is likely for aging to affect LV diastolic function more in women than in men. Global longitudinal strain appears to be higher in women during the childbearing age – a finding that also highlights a possible hormonal influence in women. All these findings have practical implications, and sex-specific reference values are necessary for the majority of echocardiographic parameters in order to distinguish normalcy from disease. Careful attention on specific cut-off points in women could avoid misinterpretation, inappropriate management and delayed treatment of cardiac diseases such as valvular disease and heart failure.